Investigative model of repurchase intention on boycott brand of multinational franchise food and beverage in Indonesia - Rizan, Mohamad; Kresnamurti, Agung; Hanoum, Farah Chalida; Anugrah, Raka Pria; Prabowo, Heri; Violinda, Qristin; Zalzalah, Guruh Ghifar; Herdiany, Hapsari Dyah (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2025)
This study aims to develop an investigative model of repurchase intention from a multidisciplinary service marketing science perspective, focusing especially on conventional and digital franchise retail services. This is supported by psychological consumer purchasing behavior to deepen the analysis of customer repurchase decisions for multinational franchise retail food and beverage products in Indonesia. Following the boycott movement against certain foreign-brand food and beverage goods, the impact of religious beliefs, hostility, and the perception of the country of origin define this process. A causal/explanatory survey was employed as the research method. Participatory observations, interviews, and questionnaires with 220 respondents were used as primary data-gathering methods. These were distributed both digitally and conventionally. Google Form in all randomly selected public and private university analysis units in Indonesia. The observation unit (respondent) used a convenience/accidental sampling technique. The analytical tool employed Lisrel version 88.0. The findings reveal that Islamic religiosity, consumer animosity, and country of origin affect repurchase intention. This original research can generate specific and relevant findings for the Indonesian market context, which companies can use to design more effective marketing, brand management, and product development strategies. This will help companies better understand their customers’ preferences and needs, as well as build stronger relationships with consumers.